2021
DOI: 10.2174/1574888x15666200628141314
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Stem Cells as a Potential Therapeutic Strategy in Neurodegenerative Disorders

Abstract: : Stem cells are considered to have significant capacity to differentiate into various cell types in humans or animals. Unlike specialized cells, these cells can proliferate several times to produce millions of cells. Nowadays, pluripotent stem cells are important candidates to provide a renewable source for replacement of cells in tissues of interest. The damage to neurons and glial cells in the brain or spinal cord is present in neurological disorders such as Amyotrophic lateral sclerosis, stroke, Parkinson’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…In the therapies of chronic heart failure (CHF) adrenergic and angiotensin signaling pathways are interrupted, while the therapies do not replace the dying myocytes during CHF progression [ 2 ]. Stem cells and some progenitor cells have recently gained much attention in cell therapy regarding the repair of damaged heart tissue [ 3 ]. In regenerative medicine, bone marrow mesenchymal stem cells (BM-MSCs) and cardiac progenitor cells play a remarkable role in the regeneration of the myocardium [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the therapies of chronic heart failure (CHF) adrenergic and angiotensin signaling pathways are interrupted, while the therapies do not replace the dying myocytes during CHF progression [ 2 ]. Stem cells and some progenitor cells have recently gained much attention in cell therapy regarding the repair of damaged heart tissue [ 3 ]. In regenerative medicine, bone marrow mesenchymal stem cells (BM-MSCs) and cardiac progenitor cells play a remarkable role in the regeneration of the myocardium [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The novel YACNSG transgenic mouse strain allows for the development of human cell transplantation products in a disease context. [27][28][29][30][31][32][33] The results from this study suggest that adult human bone marrow derived mesenchymal stem (hMSC) cells engineered to express GFP and luciferase are retained longer than the YAC128 and similar to NSG mice. Our data demonstrates that cells are rapidly cleared from the CNS when using the parental YAC128 line without immune suppression as expected.…”
Section: Discussionmentioning
confidence: 79%
“…Recent research has suggested that stem cell therapy may hold promise as a potential treatment option for acute and subacute ischemic stroke. Stem cells can differentiate into various cell types and can potentially regenerate damaged tissue, making them a promising therapeutic approach for neurological disorders such as stroke (Ebrahimi et al, 2021).…”
Section: Million Fatalitiesmentioning
confidence: 99%